Macau - poslednje portugalsko čezmorsko ozemlje - Gabrovec, Matej (Geografski obzornik, 1999)
In 1997 the British return of Hong Kong to the People's Republic of China echoed in media. At midnight of 19 December 1999 Portugal yielded Macau, Hong Kong neighbouring territory, to China. This last overseas Portuguese territory can not be compared with Hong Kong neither by the economy power nor by the number of inhabitants or the area. Despite that this is an important change on the world's political map. The article therefore presents the main geographical characterisitcs of Macau which can only be explained by its historical development.
Keywords: družbena geografija; Macau; Makao; regionalna geografija; zgodovinski pregledi